2022
DOI: 10.1007/s13127-022-00585-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of skull morphology and cranial kinesis in common toads

Abstract: We examined the cranial morphology and cranial kinesis of the common toads Bufo bufo and B. spinosus with micro-computed tomography and geometric morphometrics and compared the results with published data for related species in a phylogenetic context. The species significantly diverge in skull shape. The skull of B. spinosus is shorter and higher, with a ventral arm of the squamosal bone and the jaw articulation point positioned perpendicular to the braincase, in comparison with a more lateral position in B. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Also, body size could associate with sexual dimorphism in skin thickness (VanBuren et al, 2019). We found that the level of head skin calcification was positively related to skull size which coincided with a marked, female biased sexual size dimorphism (Arntzen, 1999; Lüscher et al, 2001; Čađenović et al, 2013; Ivanović et al, 2022; Dursun et al, 2022). Yet, the calcification level of the head skin and the parotoids cannot be solely explained by size.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Also, body size could associate with sexual dimorphism in skin thickness (VanBuren et al, 2019). We found that the level of head skin calcification was positively related to skull size which coincided with a marked, female biased sexual size dimorphism (Arntzen, 1999; Lüscher et al, 2001; Čađenović et al, 2013; Ivanović et al, 2022; Dursun et al, 2022). Yet, the calcification level of the head skin and the parotoids cannot be solely explained by size.…”
Section: Discussionmentioning
confidence: 73%
“…Fisher's exact test for count data was performed to test for statistical significance in character states frequency distribution. As an estimation of head size, we used skull size data obtained from the same individuals (centroid size values—CS; Supporting information, Table S1) from Ivanović et al (2022). To test if the individuals with different levels of calcification of dorsal skin and parotoids differ in skull size, we performed a nested ANOVA with calcification level, species and sex nested within species as factors and skull size as dependent variable.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations